Staphylococcus sp. colonization in workers from areas of hospital support: epidemiological and microbiological aspects - Larissa Oliveira Rocha Vilefort; Lara Stefânia Netto de Oliveira Leão Vasconcelos; Dayane de Melo Costa; Ana Beatriz Mori Lima; Edgar Berquó Peleja; Marinésia Aparecida do Prado (Universidade Federal de Goias, 2016)
The objectives were to determine the prevalence of workers colonized by Staphylococcus sp., to identify colonization predictors and, to assess their susceptibility to antimicrobials. A questionnaire was applied and saliva was collected in 130 workers from support areas of an oncology institution. Microbiological analysis was conducted following standard procedures.  The prevalence of workers colonized by Staphylococcus sp. was 37.7%, and the isolated majority was Staphylococcus coagulase-negative. Resistance to methicillin was detected in 35.1% of Staphylococcus coagulase-negative, being 12 epidermidis and one S. haemolyticus. From those. 92.3% had the mecA. gene. All S. aureus were sensitive to methicillin. Working shift and sector were identified as predictors for colonization. The colonization in workers from support areas assisting oncology patients indicates that workers should be target of occupational health policies, and  it should include pre- and post-colonization measures in investigations/discussions of future studies aiming at worker and patient safety.